2014
DOI: 10.1186/1471-2393-14-358
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of feto-maternal hemorrhage among rhesus D negative pregnant mothers using the kleihauer-betke test (KBT) and flow cytometry (FCM) in Addis Ababa, Ethiopia

Abstract: BackgroundThis study aimed to assess fetomaternal hemorrhage (FMH) among RhD negative pregnant mothers using two techniques, Kleihauer-Betke (KBT) and Flow cytometry (FCM). To determine if patient-specific doses of prophylactic anti-D warrant further investigation in Ethiopia and wider Africa.MethodsHospital- based cross-sectional study was conducted among 75 RhD negative pregnant mothers using convenient sampling technique.ResultFMH has been detected in 52% and 60% by KBT and FCM techniques, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
6
0
6
Order By: Relevance
“…5,11 Our result has shown that FMH occurs in 46% (27/59) of our participants after delivery using KBT. The test was negative in 54.24% (32/59) of patients, which was consistent with the study of Urgessa et al 16 that concluded FMH was negative in 48% (36/75) of their patients. The total volume of fetal cells in the maternal circulation is usually small and varies between 0.1 and 0.25 mL in most cases, but large volume of FMH occurs less often, with more than 15 mL of fetal red cells (approximately 30 mL whole blood) detected at a rate of 1.6% after cesarean section or complicated vaginal delivery and 0.7% after spontaneous vaginal delivery.…”
Section: Discussionsupporting
confidence: 91%
“…5,11 Our result has shown that FMH occurs in 46% (27/59) of our participants after delivery using KBT. The test was negative in 54.24% (32/59) of patients, which was consistent with the study of Urgessa et al 16 that concluded FMH was negative in 48% (36/75) of their patients. The total volume of fetal cells in the maternal circulation is usually small and varies between 0.1 and 0.25 mL in most cases, but large volume of FMH occurs less often, with more than 15 mL of fetal red cells (approximately 30 mL whole blood) detected at a rate of 1.6% after cesarean section or complicated vaginal delivery and 0.7% after spontaneous vaginal delivery.…”
Section: Discussionsupporting
confidence: 91%
“…FMH occurred in 17.9%, 10%, and 11.1% of the women at 16–24 weeks, 28–32 weeks, and 34–37 weeks of pregnancy, respectively. In previous studies, prevalence of FMH in the third trimester varied from 5.6% in Pakistan, to 40% in India, and 52% in Ethiopia . In 2 (1.3%) women, volume of FMH was greater than 30 mL, while in 30 (19.9%) women it was less than or equal to 30 mL.…”
Section: Discussionmentioning
confidence: 85%
“…Lo anterior permite que el operador identifique la proporción de eritrocitos fetales al interior del torrente materno, estimando mediante complejas fórmulas matemáticas la cantidad de sangre fetal (en mililitros) transfundida. 12,17,29,30 . La principal limitación del método radica en la complejidad del mismo.…”
Section: Discussionunclassified